Peran Penyuluh sebagai Agent of Change dalam Adopsi Inovasi Padi Rojolele Srinuk - Sandra Mega Prestiana; Dwiningtyas Padmaningrum; Sugihardjo Sugihardjo (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2023)
Introducing Rojolele Srinuk rice variety, an innovation from the Klaten Regency Government, and Delanggu Village is one of the villages targeted for developing these varieties. It is inseparable from the role of agricultural extension workers as agents of change in the process of adoption by farmers. As someone on behalf of the government, the agricultural extension worker is obligated to influence the decision-making process to restore Rojolele's existence in Delanggu Village. This study aimed to analyze the role of agricultural extension workers as agents of change and identify internal agents of change who play a role in adopting the Rojolele Srinuk rice innovation in Delanggu Village. The research method used in this research is a descriptive qualitative method—data collection technique with in-depth interviews with 12 informants, observation, and document study. The results showed that: 1) the role of an extension worker as the agent of change in the adoption of Rojolele Srinuk rice innovations includes: a) developing awareness of the target that needs change; b) establishing an information exchange relationship; c) to diagnose target problems; d) to create an intent to change in the target; f) to create an intent into action; g) to stabilize adoption and prevent discontinuance; h) to achieving change targets and ending dependency relationships. 2) The role of agricultural extension workers as agents of change has been good and quite good in establishing an information exchange relationship. 3) There are internal change agents in the social system who have a more significant effort in adopting Rojolele Srinuk rice innovations in persuasion and marketing.